Design methodology of a two-degrees-of-freedom gravitational energy harvester. Issue 1 (1st February 2023) - Monaco, M Lo; Russo, C
Abstract: The growing spread of IoT (Internet of Things) and monitoring system based on micro electro-mechanical system (MEMS) concerns also the railway systems. The recent developments have made it possible to study and realize innovative integrated systems using connected devices. The technologies allow to collect real-time data from assets, thus providing fundamental information regarding the operation conditions and offering an evaluation of safety and durability of the monitored device. The major innovation of these devices is the use of energy harvesters to support or replace their power supply, making the monitoring device completely autonomous and drastically lowering the maintenance costs. The work presented in this paper is the product of the research group knowledge in vibrational energy harvesting. In particular, we studied a two-degrees-of-freedom (2DOF) gravitational vibration-based energy harvester (GVEH), characterized by the absence of the magnet on the top end of the tube, exploiting gravity as a restoring force. Different masses configuration were tested in order to find the best configuration optimizing power output, frequency bandwidth and overall performances. The time-domain simulations realized in Matlab/Simulink environment are supported with Multiboduy simulations for a better understanding of the system dynamics.